2023
DOI: 10.1002/iid3.1045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the role of probiotics in modulating immune cells in ulcerative colitis

Ni Guo,
Lu‐lu Lv

Abstract: BackgroundUlcerative colitis (UC) is a persistent inflammatory disorder that affects the gastrointestinal tract, mainly the colon, which is defined by inflammatory responses and the formation of ulcers. Probiotics have been shown to directly impact various immune cells, including dendritic cells (DCs), macrophages, natural killer (NK) cells, and T and B cells. By interacting with cell surface receptors, they regulate immune cell activity, produce metabolites that influence immune responses, and control the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 137 publications
(496 reference statements)
0
2
0
Order By: Relevance
“…It is well-known that the immune dysfunction is the root cause of the dominati development of IBD [39]. In murine colitis models, there is an observed increase in t infiltration of monocytes and macrophages into the colon mucosa, which are responsi for the production of various inflammatory mediators [51,52]. In agreement with t previous report, there was a notable increase in the recruitment of neutrophils a macrophages in the colon tissues of the DSS-control group compared to the non-D control group (Figure 6A), indicating severe inflammation in the intestines [5 Numerous reports revealed that by reducing the influx of inflammatory cells into t affected intestinal tissues, the overall inflammatory burden could be significan decreased in DSS-induced colitis [53,54].…”
Section: Protective Effects Of Cmc-axt-nps On Dss-induced Inflammationmentioning
confidence: 99%
“…It is well-known that the immune dysfunction is the root cause of the dominati development of IBD [39]. In murine colitis models, there is an observed increase in t infiltration of monocytes and macrophages into the colon mucosa, which are responsi for the production of various inflammatory mediators [51,52]. In agreement with t previous report, there was a notable increase in the recruitment of neutrophils a macrophages in the colon tissues of the DSS-control group compared to the non-D control group (Figure 6A), indicating severe inflammation in the intestines [5 Numerous reports revealed that by reducing the influx of inflammatory cells into t affected intestinal tissues, the overall inflammatory burden could be significan decreased in DSS-induced colitis [53,54].…”
Section: Protective Effects Of Cmc-axt-nps On Dss-induced Inflammationmentioning
confidence: 99%
“…Previous studies show that the probiotics L. fermentum , L. gasseri , and L. reuteri not only improve gut barrier function and protect against damage to the colon mucosa but also modulate intestinal immune responses in the DSS-induced colitis model [ 1 , 24 , 25 ]. Research into the effects of probiotics in mouse models of colitis is ongoing; nevertheless, the mechanism by which probiotics support intestinal barrier function is unclear [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Currently, some drugs including aminosalicylic acid, sulfasalazine and immune‐suppressants have been clinically used to treat UC, but these medications can lead to drug tolerance and adverse reactions. [ 8 , 9 ] Therefore, it is urgent to search and develop more effective new drugs for the treatment of colitis.…”
Section: Introductionmentioning
confidence: 99%